(3GdMeGjI GdJfajPjI ddCMcGe GdEOGQjI Hjf GdJLQje hGdJCOjH hGdEdZGA hGdJYhjV (B:s (3OQGSI fXQjI hJWHjbjI aj VhA Gdabg hCMcGe GdbVGA (B/s - (3YHO GdeLjO, eMehO SYOs ((3GdEScfOQjI (B[(3eUQ(B] :s (3OGQ GdLGeYI GdLOjOI,s, 2012)
(3jfbSe GdcJGH Edi aUd JegjOj (B: (3GdefGN GdegjF ddGNdGd HJfajP GdGMcGe GdGOGQjI(B-(3GdHGH GdChd (B: (3JfajP GdGMcGe GdGOGQjI (B((3GdaUd GdGhd (B: (3TQhW JfajP GdGMcGe GdGOGQjI(B-(3GdaUd GdKGfj (B: (3GdJRGe GdGOGQI HJfajP GdMce GdGOGQj(B-(3GdaUd GdKGdK (B: (3GNdGd GdGOGQI HJfajP GdMce GdGOGQj(B) (3GdHGH GdKGfj (B: (3GdMeGjI GdbGfhfjI dJfajP GdGMcGe GdGOGQjI (B((3GdaUd GdChd (B: (3GdOYhi GdGOGQjI(B-(3GdaUd GdKGfj (B: (3GdOYhi GdLfGFjI(B-(3GdaUd GdKGdK (B: (3QbGHI eLdS GdOhdI cgjFI GSJTGQjI Ydi JfajP GdGMcGe GdGOGQjI(B)s
(3HHdjhLQGajI (B: (3UaMI (B305-312.s
Keywords: (3GdJYhjVGJs -- (3bhGfjf hJTQjYGJs; (3bVGA GdEdZGAs; (3GdESdGe hGdbGfhf GdEOGQjs; (3GdbGfhf GdEOGQjs -- (3eUQs